2020
DOI: 10.1101/2020.06.02.129288
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Calmodulin binds to the N-terminal domain of the cardiac sodium channel Nav1.5

Abstract: 1The cardiac voltage-gated sodium channel Nav1.5 conducts the rapid inward sodium current crucial for 2 cardiomyocyte excitability. Loss-of-function mutations in its gene SCN5A are linked to cardiac arrhythmias 3 such as Brugada Syndrome (BrS). Several BrS-associated mutations in the Nav1.5 N-terminal domain exert 4 a dominant-negative effect (DNE) on wild-type channel function, for which mechanisms remain poorly 5 understood. We aim to contribute to the understanding of BrS pathophysiology by characterizing t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
2
1
Order By: Relevance
“…Previous research suggested that the residues between 493 and 517 are critical for the dimerization and coupled gating of NaV1.5 at the cell surface, and another study found an enrichment of dominant negative variants at the N-terminus of the protein (8,29). We did not observe an enrichment of dominant negative variants among these previously described residues, but rather a broader distribution of variants spanning the four transmembrane domains of the protein (Figure 6A-6C).…”
Section: Dominant Negative Effect Among Most Missense Lof Scn5a Variantscontrasting
confidence: 53%
“…Previous research suggested that the residues between 493 and 517 are critical for the dimerization and coupled gating of NaV1.5 at the cell surface, and another study found an enrichment of dominant negative variants at the N-terminus of the protein (8,29). We did not observe an enrichment of dominant negative variants among these previously described residues, but rather a broader distribution of variants spanning the four transmembrane domains of the protein (Figure 6A-6C).…”
Section: Dominant Negative Effect Among Most Missense Lof Scn5a Variantscontrasting
confidence: 53%
“…Unlike potassium channel genes, which encode one fourth of tetramers constituting functional channels, Na v 1.5 channels were thought to be structured as monomers, since the gene encodes the entire 4domain channel α-subunit. It was thus unexpected to report Na v 1.5 mutants with a dominant-negative effect on wildtype (WT) channels, i.e., a decrease of I Na exceeding the 50% of current density expected in case of haploinsufficiency observed when coexpressing some mutants with WT channels in a 1:1 ratio to mimic patient heterozygosity, as we and others did [2][3][4][5][6][7][8][9]. Furthermore, we demonstrated that Na v 1.5 α-subunits could interact with each other and that a trafficking-efficient mutant channel was able to drive a trafficking-deficient one to the surface membrane [3].…”
Section: Introductionmentioning
confidence: 68%
“…Follow up studies with extensive biochemical analyses showed that the dominant negative variant L325R acted through coupled gating at the cell surface (9). Previous research suggested that the residues between 493 and 517 are critical for the dimerization and coupled gating of NaV1.5 at the cell surface, and another study found an enrichment of dominant negative variants at the N-terminus of the protein (8,29). We did not observe an enrichment of dominant negative variants among these previously described residues, but rather a broader distribution of variants spanning the four transmembrane domains of the protein (Figure 6A-6C).…”
Section: Dominant Negative Effect Among Most Missense Lof Scn5a Variantsmentioning
confidence: 99%